Recent Advances of COVID-19 Modeling Based on Regenerative Medicine - Larijani, Bagher; Foroughi-Heravani, Najmeh; Abedi, Mina; Tayanloo-Beik, Akram; Rezaei-Tavirani, Mostafa; Adibi, Hossein; Arjmand, Babak (Frontiers in Cell and Developmental Biology, 2021)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has caused a pandemic since December 2019 that originated in Wuhan, China. Soon after that, the world health organization declared Coronavirus disease-2019 a global health concern. SARS-CoV-2 is responsible for a lethal respiratory infection as well as the involvement of other organs due to its large tropism spectrum such as neurologic, cardiovascular, endocrine, gastrointestinal, and renal systems. Since the behavior of the virus is not fully understood, a new manifestation of the infection is revealed every day. In order to be able to design more efficient drugs and vaccines to treat the infection, finding out the exact mechanism of pathogenicity would be necessary. Although there have been some big steps toward understanding the relevant process, there are still some deficiencies in this field. Accordingly, regenerative medicine (RM), can offer promising opportunities in discovering the exact mechanisms and specific treatments. For instance, since it is not always possible to catch the pathophysiology mechanisms in human beings, several modeling methods have been introduced in this field that can be studied in three main groups: stem cell-based models, organoids, and animal models. Regarding stem cell-based models, induced pluripotent stem cells are the major study subjects, which are generated by reprogramming the somatic stem cells and then directing them into different adult cell populations to study their behavior toward the infection. In organoid models, different cell lines can be guided to produce a 3D structure including liver, heart, and brain-like platforms. Among animal models, mice are the most common species in this field. However, in order for mice models to be permissive to the virus, angiotensin-converting enzyme 2 receptors, the main receptor involved in the pathogenicity of the virus, should be introduced to the host cells through different methods. Here, the current known mechanism of SARS-CoV-2 infection, different suggested models, the specific response toward different manipulation as well as challenges and shortcomings in each case have been reviewed. Finally, we have tried to provide a quick summary of the present available RM-based models for SARS-CoV-2 infection, as an essential part of developing drugs, for future therapeutic goals.